2002
DOI: 10.1177/070674370204700203
|View full text |Cite
|
Sign up to set email alerts
|

The Neurobiology of Bipolar Disorder: Focus on Signal Transduction Pathways and the Regulation of Gene Expression

Abstract: Despite the difficulties inherent in biochemical studies of clinically relevant tissue samples, numerous investigations have illuminated the signal transduction mechanisms in patients with BD. These studies also suggest that BD may be due to the interaction of many abnormalities. In this context, novel techniques enabling the study of gene expression promise to assist in untangling these complex interactions, through visualizing the end result of these changes at the level of gene transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 158 publications
(142 reference statements)
4
51
0
2
Order By: Relevance
“…The a1 receptors have also been found to activate other signal transduction systems, such as the mitogen activated protein kinase and cAMP pathways (Michelotti et al, 2000;Piascik and Perez, 2001). Much research has demonstrated that lithium treatment affected cAMP pathways (Bezchlibnyk and Young, 2002). Together with our finding that lithium decreased a1B-AR expression, this suggests that the a1B-AR coupled signaling may be a pathway with multiple targets for lithium.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The a1 receptors have also been found to activate other signal transduction systems, such as the mitogen activated protein kinase and cAMP pathways (Michelotti et al, 2000;Piascik and Perez, 2001). Much research has demonstrated that lithium treatment affected cAMP pathways (Bezchlibnyk and Young, 2002). Together with our finding that lithium decreased a1B-AR expression, this suggests that the a1B-AR coupled signaling may be a pathway with multiple targets for lithium.…”
Section: Discussionsupporting
confidence: 76%
“…Prophylactic treatment with lithium prevents recurrences of depression and mania in a substantial proportion of patients with this disorder (Davis et al, 1999). Much research has shown that lithium regulates components of signal transduction pathways and their downstream gene transcription factors, an indication that changes in gene expression are likely to underlie the mechanism of action of the treatment (Manji and Zarate, 2002;Bezchlibnyk and Young, 2002). Lithium-induced changes in gene expression have been documented in both cultured cells and animal models (Kalasapudi et al, 1990;Williams and Jope, 1994;Manji et al, 1995a, b).…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of studies looking at the effects of lithium, an effective prophylactic treatment for BD, on CREB DNA binding, as well as its effects on gene expression. They all concur in that lithium decreases CREB phosphorylation leading to inefficient DNA binding resulting in altered expression of cAMP responsive genes (Bezchlibnyk and Young, 2002). Thus it is possible that genetic variation in genes coding for CREB proteins may help determine response to lithium prophylaxis.…”
Section: Introductionmentioning
confidence: 85%
“…Among the multiple cell signal transduction pathways, the cAMP signaling has drawn particular interest (Tardito et al, 2000;Stewart et al, 2001;Bezchlibnyk and Young, 2002), and hyperfunction of cAMP and downstream targets has been postulated for the etiopathology of BAD (Young et al, 1993;Perez et al, 1999). The first cAMP signal target is protein kinase A (PKA), an important phosphorylating enzyme that activates the transcription factors, that is, the cAMP responsive element binding (CREB) protein, and controls the expression of critical genes such as brain-derived neurotrophic factor (BDNF) (Shieh and Ghosh, 1999).…”
Section: Introductionmentioning
confidence: 99%